Change in quality of life after treatment of mild velopharyngeal insufficiency with autologous fat transplantation - D. Impieri; K.A. Tønseth; Ø. Hide; K.J.B. Feragen; H.E. Høgevold; C. Filip (JPRAS Open, 2017)
Background: Autologous fat transplantation has been used to treat mild velopharyngeal insufficiency (VPI) for the last two decades. The effectiveness of this technique has been evaluated by assessing speech and measuring velopharyngeal closure. Few studies have considered the subjective opinion of the patient and their parents. This study aimed to evaluate the quality of life (QOL) of patients who had undergone fat transplantation using a validated questionnaire, VPI Effects on Life Outcome (VELO). Patients and methods: Two copies of the questionnaire VELO were administered to 26 patients with mild VPI who had undergone fat transplantation between 2006 and 2015. All patients were nonsyndromic, and 17 of them had cleft palate. All clefts had been repaired prior to fat transplantation. Both patients and their parents, for those younger than 18 years, completed two questionnaires each: the first one referred to the preoperation QOL, while the second one referred to the current QOL. Results: The total score and “Speech limitations,” “Situational difficulty,” and “Emotional impact” subscores improved significantly (p < 0.005) when assessed by the patients. A significant improvement was also observed in the total score and “Speech limitations” subscore when assessed by the parents (p = 0.008). A significant improvement in QOL was found in cleft palate patients (p = 0.004). Better improvement in QOL was found in patients who had undergone fat transplantation more than 3 years ago (p = 0.001) and in those who had undergone only one procedure (p = 0.009). Conclusions: Fat transplantation to the velopharynx improves the QOL in patients with mild VPI.